Market transparency and the marking precision of bond mutual fund managers - Gjergji Cici; Scott Gibson; Yalin Gündüz; John J. Merrick (Deutsche Bundesbank, 2014)
We analyze the dispersion of month-end price marks simultaneously placed on identical corporate bonds by different US mutual fund managers before and after initiations of TRACE and introductions of issuers into Markit's CDS database. Disseminated bonds show large and statistically significant decreases in mark dispersion around three key TRACE system rollout events. Dispersion for large, investment grade bonds fell 20% to 83% after the start of TRACE reporting. A difference-in-differences regression analysis of the two-stage rollout of BBB-rated bonds provides clearer evidence suggesting that TRACE led to a decrease in price dispersion. TRACE-associated decreases in crossfund bond mark dispersion provide indirect support for Bessembinder, Maxwell, and Venkataraman's (2006) information-based channel relating transparency and pricing. During the pre-TRACE period, we also find some evidence that mark dispersion fell for investment grade issuers after introductions into Markit's database.
Keywords: G12; G23; 330; TRACE; CDS; bonds; transparency; marks